Historical improvement in speed skating economy - Noordhof, D. A.; van Tok, E.; Joosten, F. S. J. G. M.; Hettinga, F. J.; Hoozemans, M. J. M.; Foster, C.; de Koning, J. J. (International Journal of Sports Physiology and Performance, 2017)
Half the improvement in 1500-m speed-skating world records can be explained by technological innovations and the other half by athletic improvement. It is hypothesized that improved skating economy is accountable for much of the athletic improvement. Purpose: To determine skating economy in contemporary athletes and to evaluate the change in economy over the years. Methods: Contemporary skaters of the Dutch national junior team (n = 8) skated 3 bouts of 6 laps at submaximal velocity, from which skating economy was calculated (in mL O2/kg·km). A literature search provided historic data on skating velocity and submaximal V.O2 (in mL/kg·min), from which skating economy was determined. The association between year and skating economy was determined using linear-regression analysis. Correcting the change in economy for technological innovations resulted in an estimate of the association between year and economy due to athletic improvement. Results: A mean (± SD) skating economy of 73.4 ± 6.4 mL O2/kg·km was found in contemporary athletes. Skating economy improved significantly over the historical time frame (-0.57 mL O2/kg·km · y-1, 95% confidence interval [-0.84, -0.31]). In the final regression model for the klapskate era, with altitude as confounder, skating economy improved with a nonsignificant -0.58 mL O2/kg·km · y-1 ([-1.19, 0.035]). Conclusions: Skating economy was 73.4 ± 6.4 mL O2/kg·km in contemporary athletes and improved over the past ~50 y. The association between year and skating economy due to athletic improvement, for the klapskate era, approached significance, suggesting a possible improvement in economy over these years.